Characterizations of specific mechanical behaviors for metallic materials with representative crystal structures using nanoindentation. (January 2023) - Si, Bowen; Li, Zhiqiang; Yang, Xuexia; Shu, Xuefeng; Xiao, Gesheng
Abstract: In some engineering applications, metallic materials with various crystal structures are widely studied for their particular mechanical properties in specific working conditions, especially in the field of micro and nano processing and manufacturing. In this study, indentation size effects (ISE) at the microscopic scale for metallic materials with different indentation strain rates are investigated, the hardness related to indentation depth and indentation loading data are corrected by removing the ISE for different crystal structured materials with nanoindentation testing technique. As a result of the different crystal structures, the indentation strain rate sensitivity indexes with and without ISE show different trends. Meanwhile, the relationship between the plastic strain gradient work as a result of ISE and the indentation strain rate is analyzed to reflect the differences in varying crystal structured materials. For different indentation strain rates and crystal structures, the percentage of plastic work to total work and the plastic work show different variation trends accordingly. The dependence of various parameters on indentation strain rate is obtained from the above analyses, which provides a foundation for the subsequent studies on mechanical properties of different crystal structured metals/alloys. Highlights: Indentation size effect (ISE) of three crystal structured metallic materials (FCC, BCC and HCP) are analyzed and eliminated. Indentation hardness and indentation strain rate sensitivity index for three metallic materials with and without ISE are identified. Indentation plastic work and plastic strain gradient work considering ISE at different indentation strain rates are acquired and analyzed.